Optimization of inulinase production by a newly isolated Penicillium amphipolaria strain using solid-state fermentation of hardy sugarcane stems. (November 2020) - Das, Deblina; Bhat M, Ramananda; Selvaraj, Raja
Abstract: A new producer of fungal inulinase Penicillium amphipolaria KAS 2555, has been isolated from the soil area of dead mangroves litter in Herikudru island, followed by the production and optimization of inulinase enzyme by solid-state fermentation (SSF) utilizing a cheap substrate – hardy sugarcane ( Saccharum arundinaceum ) stems. During the screening process, only P.amphipolaria KAS 2555 displayed a zone of hydrolysis on the inulin media. Thin-layer chromatography (TLC) confirmed the action pattern and the exoinulolytic nature of the inulinase enzyme. After 4 days of fermentation, 2.45 U/gds activity was obtained. The inulolytic nature of the inulinase was proven by obtaining 0.59 I/S ratio. The optimization of media was carried out to obtain a regression model using central composite design. Five media constituents viz., inulin, (NH4 )2 SO4, K2 HPO4, KH2 PO4, and, NaCl were used for optimization. The coefficient of determination (R 2 ) calculated was 0.9490 for the inulinase activity. An inulinase activity of 7.59 U/gds (3.1 times higher than non-optimized medium) was observed at optimal conditions: (g/gds) inulin- 0.1, (NH4 )2 SO4 - 0.002, K2 HPO4 - 0.1, KH2 PO4 - 0.02 and NaCl- 0.02. Graphical abstract: Image 1 Highlights: Penicillium amphipolaria KAS 2555, a new inulinase producer was isolated from detritus mangrove soil. Saccharum arundinaceum proved to be an efficient substrate for solid state fermentative production of inulinase. Central Composite Design was used to optimize the five media components namely, inulin, K2 HPO4, (NH4 )2 SO4, KH2 PO4 and NaCl. Under the optimum conditions, a 3.10-fold increase in inulinase activity was obtained.